Safety of Magnetic Resonance Imaging in Patients with Cardiac Implantable Electronic Devices - Hugo Lanz; Katharina Strauß; Julia Höpler; Marie Kraft; Sabine Hoffmann; Leonhard Binzenhöfer; Nils Gade; Daniel Roden; Inas Saleh; Stefan Kääb; Korbinian Lackermair; Sebastian Sadoni; et al. (Journal of Cardiovascular Development and Disease)
Background: MRI (magnetic resonance imaging) represents the diagnostic image modality of choice in several conditions. With an increasing number of patients requiring MRI for diagnostic purposes, the issue of safety in patients with cardiac implantable electronic devices (CIED) undergoing this imaging modality will play an ever more important role. The purpose of this study was to assess the safety and device function following MRI in an unrestricted real-world cohort of patients with a wide array of cardiac devices. Methods: We conducted a retrospective single-center study including 1010 MRI studies conducted in adult patients (≥18 years) with an implanted CIED treated in the University Hospital of Munich (LMU) between July 2012 and March 2024. Patients with non-MR conditionally labeled leads, abandoned or epicardial leads, as well as lead fragments, were included for analysis. Results: Across a total of 1010 MRIs (920 total MR-conditional device generators) performed in patients with an implanted CIED, there were no deaths, reports of discomfort, palpitations, heating, or ventricular arrythmias in the 24 h following MRI. Only 2/1010 MRIs were followed by a reported atrial arrhythmia within 24 h, both in patients with an MR-conditional pacemaker (PM) device without an abandoned lead. No significant changes in device function following MRI from baseline were observed across all included CIEDs. Lastly, no instances of severe malfunction, such as generator failure, loss of capture, electrical reset, or inappropriate inhibition of pacing, were found in post-MRI interrogation reports across all MRI studies. Conclusions: Based on the analysis of 1010 MRIs undergone by patients with CIEDs, following standardized device interrogation, manufacturer-advised device programming, monitoring of vital function, and manufacturer-advised reprogramming, MRI can be performed safely and without adverse events or changes in device function.